Atopolis. - Pirenne, Raphaël; Biset, Sébastien; Pirenne, Raphaël (Brussels : WIELS, 2015)
Afif, Saâdane ; Aladaǧ, Nevin ; Alÿs, Francis ; Anatsui, El ; Anesiadou, Danai ; Barrada, Yto ; Beeckman, Vincen ; Beshty, Walead ; Bhabha, Huma ; Caniaris, Vlassis ; et al.
Publicatie n.a.v. de tentoonstelling in Manège de Sury te Bergen van 13 juni tot 18 oktober 2015
boek